(untitled) (Journal of actual problems of jurisprudence, 2019)
In the scientific article describes the historical background of the development of related rights. The research of the major historical stages of legislation for the protection of performers, producers of phonograms, the rights of broadcasting organizations. The research covers the history of the world and its impact on the development of related rights in the Republic of Kazakhstan. As a final positions we find basic directions of development of legislation related rights in Kazakhstan. Keywords: related rights, the rights of performers, producers of phonograms, the rights of broadcasting organizations.